208k views
4 votes
5(x^3)^2(-2x^4)^-3

Simplify and write with positive exponents

P.s that isn’t minus 3, it is exponent -3

User Erresen
by
5.0k points

1 Answer

4 votes

Answer:

20480x^18

Explanation:

first of all, solve 5(x^3)^2

(x^3)^2 means 3x2=6, so x^6. 5 times x^6 = 5x^6

(16x^4)^-3 = 1/4096x^-12

when theres a negative in exponent, make it 1/y.

when negative exponent appears in 1/y just flip it again to make it y. So...

5x^6 ( 4096x^12) = 20480x^18

hope this helps.

User Dawid Karabin
by
5.0k points